2018
DOI: 10.1039/c7tx00260b
|View full text |Cite
|
Sign up to set email alerts
|

The systemic toxicity of heavy metal mixtures in rats

Abstract: To explore the health effects of multi-heavy metal exposure, Sprague Dawley (SD) rats were orally given one dose of heavy metal mixtures (HMMs). The eight most common detectable heavy metals in Ningbo area are zinc (Zn), copper (Cu), manganese (Mn), chromium (Cr), nickel (Ni), cadmium (Cd), lead (Pb) and mercury (Hg). In this study, mixtures of these eight heavy metals were prepared using the compounds zinc sulfate heptahydrate, cupric sulfate, manganese dichloride, potassium dichromate, nickel dichloride, cad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 17 publications
3
25
0
Order By: Relevance
“…Recent rat intraperitoneal toxicity studies and mathematical modeling of binary and/or ternary combinations of manganese, chromium (VI) and nickel demonstrated additivity and/or subadditivity of combined subchronic toxicity effects [240,241]; these effects were influenced by dose, effect level, and type of effect assessed. In another study, with oral gavage administration of soluble forms of zinc, copper, manganese, chromium, cadmium, lead, mercury and nickel to rats, systemic toxicity, mortality and effects on neurobehavioral function were observed dose-dependently at the two highest mixture exposure levels of 464 and 1000 mg/kg bw [242]. Here, the interactions (such as antagonism, synergism, additivity) were not accounted for.…”
Section: Mixturesmentioning
confidence: 98%
“…Recent rat intraperitoneal toxicity studies and mathematical modeling of binary and/or ternary combinations of manganese, chromium (VI) and nickel demonstrated additivity and/or subadditivity of combined subchronic toxicity effects [240,241]; these effects were influenced by dose, effect level, and type of effect assessed. In another study, with oral gavage administration of soluble forms of zinc, copper, manganese, chromium, cadmium, lead, mercury and nickel to rats, systemic toxicity, mortality and effects on neurobehavioral function were observed dose-dependently at the two highest mixture exposure levels of 464 and 1000 mg/kg bw [242]. Here, the interactions (such as antagonism, synergism, additivity) were not accounted for.…”
Section: Mixturesmentioning
confidence: 98%
“…Outside the central nervous system, Mn exposure is understood to be a carcinogen and has been implicated in multiple forms of cancer [136][137][138][139]. In prostate cancer cells, it was found that an upregulation of miR17* following Mn exposure yielded a protective effect in PC-3 cells, significantly reducing the tumorigenicity of the cell line [39].…”
Section: Manganese-associated Changes In Mirna Expressionmentioning
confidence: 99%
“…There are reports 31,32 of decreased renal function, hepatic injuries and disturbance in the electrolyte balance of rats treated with a high dose of heavy metal mixture. The present work demonstrates a significant increase in relative weights of the spleen, and immune system-related organ.…”
Section: Fig 5: Changes In the Relative Spleen Weight (G / 100 G Bodmentioning
confidence: 99%